The Capax in a New Key: Kierkegaard's Development of Classical Lutheran Christology - Boehmer, David (Toronto journal of theology, 2017)
This article examines Kierkegaard's relationship with classical Lutheran Christology. It does so in terms of the claim that the finite has the capacity for the infinite ( finitum capax infiniti—henceforth capax), a classical Lutheran claim according to which Christ's finite humanity completely grasps his infinite divinity. Though Kierkegaard's treatment of transcendence has tended to receive more attention, a doctrine of radical immanence also appears to permeate his thought—a doctrine reminiscent of the capax. Yet he writes at some distance from the claim's original framers. The question thus arises: is Kierkegaard's treatment of Christ in keeping with their expression of the capax? With special reference to Luther and the Lutheran scholastic Johann Gerhard, I argue the affirmative: that is—in their treatment of subjectivity—Kierkegaard's idea of Christ's incognito and his understanding of Christ as God's infinite redoubling represent developments concerning the essential logic of the capax. In Christ, God makes himself entirely present, yet hidden in order to preserve the subjectivity of his followers, and God preserves his own subjectivity as well, perfectly reproducing it in his human life. Understanding this creative development of the capax helps situate Kierkegaard with respect to the Lutheran tradition and sheds light on his ideas of redoubling, incognito, and the God-human being.